2006
DOI: 10.1002/hep.21158
|View full text |Cite
|
Sign up to set email alerts
|

Mrp4−/− mice have an impaired cytoprotective response in obstructive cholestasis

Abstract: Mrp4 is a member of the multidrug resistance-associated gene family that is expressed on the basolateral membrane of hepatocytes and undergoes adaptive upregulation in response to cholestatic injury or bile acid feeding. However, the relative importance of Mrp4 in a protective adaptive response to cholestatic injury is not known. To address this issue, common bile duct ligation (CBDL) was performed in wild-type and Mrp4؊/؊ mice and animals followed for 7 days. Histological analysis and serum aminotransferase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 50 publications
(79 reference statements)
7
137
0
Order By: Relevance
“…Studies in cell culture 14,15 and in animal models [15][16][17][18] have shown increased hepatic MRP4/Mrp4 mRNA and protein expression under cholestatic conditions. Moreover, Mennone et al 19 showed that serum bile acid levels are lower in Mrp4 knockout mice than in wild-type CBDL (common bile duct ligation) mice, indicating a role of murine Mrp4 in the adaptive response to obstructive cholestatic liver injury. Keitel et al 20 reported a significant increase in MRP4 mRNA and protein expression in a small number of liver samples from children diagnosed with PFIC-2 and -3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cell culture 14,15 and in animal models [15][16][17][18] have shown increased hepatic MRP4/Mrp4 mRNA and protein expression under cholestatic conditions. Moreover, Mennone et al 19 showed that serum bile acid levels are lower in Mrp4 knockout mice than in wild-type CBDL (common bile duct ligation) mice, indicating a role of murine Mrp4 in the adaptive response to obstructive cholestatic liver injury. Keitel et al 20 reported a significant increase in MRP4 mRNA and protein expression in a small number of liver samples from children diagnosed with PFIC-2 and -3.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, in vitro experiments 14,15 as well as animal models [15][16][17][18] of cholestasis have demonstrated that human MRP4 and rodent Mrp4 are induced under cholestatic conditions. Mennone et al 19 showed that serum bile acid concentrations are lower in Mrp4 knockout mice than in wild-type CBDL (common bile duct ligation) mice presumably owing to impaired secretion of bile acids over the basolateral hepatocyte membrane. Moreover, the upregulation of MRP4 mRNA and protein in human liver has been reported for a small number of liver specimens from children diagnosed with progressive familial intrahepatic cholestasis (PFIC)-2 and 3.…”
Section: Introductionmentioning
confidence: 99%
“…Mrp4 plays an essential protective role in the adaptive response to obstructive cholestatic liver injury. 29 Therefore, we could not attribute the better tolerance of cholestasis in LIGFREKO mice to enhanced adaptive transport.…”
Section: A Role For Adaptive Transport Mechanisms In Liver Protectionmentioning
confidence: 94%
“…Liver samples were homogenized in a 1:1 solution of t-butanol/water (approximately 200 mg of liver/ml) and extracted overnight as described previously (Mennone et al, 2006). Samples were centrifuged at 10,000g for 20 min, and the supernatant was removed and placed in a SpeedVac (Thermo Fisher Scientific, Waltham, MA) until dry.…”
Section: Methodsmentioning
confidence: 99%